The Correlation between Error Correction and Grammar Accuracy in Second Language Writing - Mawlood Hussein, Shivan; Bensen Bostanci, Hanife (International Journal of Psychosocial Rehabilitation, 2020)
Error correction is not considered a recent arena in language acquisition. However, it has a great effect on the language education process; further error correction has a significant role in the process of learning languages. The aim of the current study is to improve students’ accuracy in terms of grammar, which is an essential part of writing composition. This study is a quantitative study based on achieved data from pre-test writing composition and post-test writing composition in order to examine the grammar accuracy of students’ writing. The participants of the study were 72 EFL students in Erbil, Iraq, who were taking English language courses at Dwarozh Institute for Teaching and Training. The findings illustrate that learners’ grammatical errors in the experimental group significantly decreased in the post-test due to checking the instructors’ error correction and rewriting the pre-test composition in the correct format. In contrast, learners’ grammatical errors in the control group are not significantly decreased in the post-test, while learners only check the instructors’ error correction without rewriting the pre-test composition in the correct format. In conclusion, error correction can be measured as an effective feature in improving students writing skills. The intention of student feedback in writing composition is to improve learners’ writing skills in addition to providing learners with effective writing, minimum error, and maximum clarity.